Epidermal morphology of pinnae of Angiopteris, Danaea and Marattia - Rolleri, Cristina Hilda (1991)
This is a study of adult epidermis morphology in 17 species of Angiopteris Hoffm., Danaea Sm., and Marattia Swz. Epidermal patterns, adult stomata, indument, and idioblasts were studied. Is the first detailed study dealing with pinna and pinnule indument in the Marattiaceae, and conclusions strongly point out that epidermal characters are diagnostic at the species level in the Marattiaceae and speculated on generic affinities within the Marattiales.